A noncanonical role of roX RNAs in autosomal epigenetic repression - Jianjian Li; Shuyang Xu; Zicong Liu; Liuyi Yang; Zhe Ming; Rui Zhang; Wenjuan Zhao; Huipai Peng; Jeffrey J. Quinn; Manyin Wu; Yushan Geng; Yuying Zhang; et al. (Nature Communications)
Abstract Long noncoding RNAs known as roX (RNA on the X) are crucial for male development in Drosophila, as their loss leads to male lethality from the late larval stages. While roX RNAs are recognized for their role in sex-chromosome dosage compensation, ensuring balanced expression of X-linked genes in both sexes, their potential influence on autosomal gene regulation remains unexplored. Here, using an integrative multi-omics approach, we show that roX RNAs not only govern the X chromosome but also target genes on autosomes that lack male-specific lethal (MSL) complex occupancy, together with Polycomb repressive complexes (PRCs). We observed that roX RNAs colocalize with MSL proteins on the X chromosome and PRC components on autosomes. Intriguingly, loss of roX function reduces X-chromosomal H4K16ac levels and autosomal H3K27me3 levels. Correspondingly, X-linked genes display reduced expression, whereas many autosomal genes exhibit elevated expression upon roX loss. Our findings propose a dual role for roX RNAs: activators of X-linked genes and repressors of autosomal genes, achieved through interactions with MSL and PRC complexes, respectively. This study uncovers the unconventional epigenetic repressive function of roX RNAs with PRC interaction.